2018
DOI: 10.3847/1538-4357/aac32c
|View full text |Cite|
|
Sign up to set email alerts
|

SN 2017ein and the Possible First Identification of a Type Ic Supernova Progenitor

Abstract: We have identified a progenitor candidate in archival Hubble Space Telescope (HST) images for the Type Ic supernova (SN Ic) SN 2017ein in NGC 3938, pinpointing the candidate's location via HST Target of Opportunity imaging of the SN itself. This would be the first identification of a stellar-like object as a progenitor candidate for any SN Ic to date. We also present observations of SN 2017ein during the first ∼49 days since explosion. We find that SN 2017ein most resembles the well-studied SN Ic SN 2007gr. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 102 publications
(172 reference statements)
10
67
0
Order By: Relevance
“…Thus despite their high luminosities they may be challenging to observe, requiring ultraviolet, or very blue-sensitive optical, detectors. Supernova 2017ein, the only SN Ic to have a progenitor system identified so far, occurred at a redshift ∼0.0027, with the candidate identified in archival Hubble Space Telescope (HST) imaging (Van Dyk et al 2018;Kilpatrick et al 2018). The star, if single, had an absolute F555W magnitude of −7.5.…”
Section: Future Possibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus despite their high luminosities they may be challenging to observe, requiring ultraviolet, or very blue-sensitive optical, detectors. Supernova 2017ein, the only SN Ic to have a progenitor system identified so far, occurred at a redshift ∼0.0027, with the candidate identified in archival Hubble Space Telescope (HST) imaging (Van Dyk et al 2018;Kilpatrick et al 2018). The star, if single, had an absolute F555W magnitude of −7.5.…”
Section: Future Possibilitiesmentioning
confidence: 99%
“…The shading represents the number density of models. Observed progenitors (in black) include the vanishing star N6946-BH1 (marked by a cross, Adams et al 2017), for which we have adjusted the luminosity to reflect an updated distance estimate (Eldridge & Xiao 2019), SN 1987A (marked by a star in the IIP section, Walborn et al 1987), several IIP SNe from Smartt (2015), type IIb and IIL SNe (both classified as II-other, and marked by dots and crosses respectively, Smartt 2015), SN 1993J (also a IIb event, Aldering et al 1994), the Ib progenitor of SN iPTF13bvn (Eldridge & Maund 2016) and finally the candidate Ic progenitor of SN 2017ein (Van Dyk et al 2018). The marked luminosity for 2017ein is an upper estimate, assuming that it was a single star (Kilpatrick et al 2018).…”
Section: Classification Of Core-collapse Progenitor Modelsmentioning
confidence: 99%
“…In recent years, a larger number of possible SE-SN progenitor detections have been published. Van Dyk et al (2018) and Kilpatrick et al (2018) studied the first possible identification of a SN Ic progenitor (SN 2017ein). Both concluded that the visible point source was consistent with a ≥45 M initial mass progenitor, however later observations are required to determine whether the point source is the actual progenitor or a compact cluster 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some single massive (M i > 25 M ) WR star SE SN progenitors have been successfully identified or modelled (e.g Crowther 2007;Dessart et al 2011;Mazzali et al 2017;Prentice et al 2018),. including the first Type Ic SN progenitor identification(Van Dyk et al 2018;Kilpatrick et al 2018).…”
mentioning
confidence: 99%